Pengaruh Ekstrak Kayu Manis (Cinnamomum sp.) dan Pembekuan terhadap Fisiologi Ikan Mas (Cyprinus carpio): Effect of Cinnamon (Cinnamomum sp.) Extract and Freezing on the physiology of Common Carp (Cyprinus carpio) - Ruddy Suwandi; Fafa Rizkon Karima; Agoes M Jacoeb; Roni Nugraha (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Post-harvest live fish distribution can be pretreated with anesthetics to reduce stress levels of the fish. A compound from natural plants such as cinnamon can be used as an anesthetic. This study was aimed to determine the effect of cinnamon extract on the fainting time of common carp, and to determine the effect of freezing shock duration on the survival rate, blood glucose levels, eye, and gill condition. The fish in cinnamon extract 1% was readily lost of consciousness after 1.58±0.04 minutes. The survival rate of stunned fish after freezing reached 100%. Meanwhile, a 45-minute freezing shock without stunning resulted in the 100% survival rate, but at 60 and 75 minutes, the survival rate was down to 88.89% and 66.67%, respectively. The freezing shock caused bleeding and damage to the gill filaments and increased the blood glucose value of the fish.